PvML1 suppresses bacterial infection by recognizing LPS and regulating AMP expression in shrimp - Wang, Yue; Yang, Li-Guo; Feng, Guang-Peng; Yao, Zong-Li; Li, Shou-Hu; Zhou, Jun-Fang; Fang, Wen-Hong; Chen, Yi-Hong; Li, Xin-Cang (Frontiers in Immunology, 2022)
Toll and Toll-like receptors (TLRs) play essential roles in the innate immunity of Drosophila and mammals. Recent studies have revealed the presence of Toll-mediated immune signaling pathways in shrimp. However, the recognition and activation mechanism of Toll signaling pathways in crustaceans remain poorly understood due to the absence of key recognition molecules, such as peptidoglycan recognition proteins. Here, a novel MD2-related lipid-recognition (ML) member named PvML1 was characterized in Penaeus vannamei. We found that PvML1 shared a similar 3D structure with human MD2 that could specifically recognize lipopolysaccharides (LPS) participating in LPS-mediated TLR4 signaling. PvML1 was highly expressed in hemocytes and remarkably upregulated after Vibrio parahemolyticus challenge. Furthermore, the binding and agglutinating assays showed that PvML1 possessed strong binding activities to LPS and its key portion lipid A as well as Vibrio cells, and the binding of PvML1 with bacterial cells led to the agglutination of bacteria, suggesting PvML1 may act as a potential pathogen recognition protein upon interaction with LPS. Besides, coating V. parahemolyticus with recombinant PvML1 promoted bacterial clearance in vivo and increased the survival rate of bacterium-challenged shrimp. This result was further confirmed by RNAi experiments. The knockdown of PvML1 remarkably suppressed the clearance of bacteria in hemolymph and decreased the survival rate of infected shrimp. Meanwhile, the silencing of PvML1 severely impaired the expression of a few antimicrobial peptides (AMPs). These results demonstrated the significant correlation of bacterial clearance mediated by PvML1 with the AMP expression. Interestingly, we found that PvML1 interacted with the extracellular region of PvToll2, which had been previously shown to participate in bacterial clearance by regulating AMP expression. Taken together, the proposed antibacterial model mediated by PvML1 might be described as follows. PvML1 acted as a potential recognition receptor for Gram-negative bacteria by binding to LPS, and then it activated PvToll2-mediated signaling pathway by interacting with PvToll2 to eliminate invading bacteria through producing specific AMPs. This study provided new insights into the recognition and activation mechanism of Toll signaling pathways of invertebrates and the defense functions of ML members.